Материалы к фауне кокцинеллид Крыма - Мизер, А.В. (Вестник зоологии, 1969)
Forty species (27 genera) were detected as a result of studying the fauna of the Crimean Coccinellidae. In all 51 species of the family Coccinellidae were registered in the Crimea. The mountain and steppe Crimea was investigated. The Coccinellidae fauna of the steppe Crimea is represented by 18 species. Steppe xerophils prevail here as to ecological forms. The Mediterranean zone, mountain-steppe slopes, mountain forests and yaila were investigated in the mountain Crimea. 24 species of Coccinellidae with mezophils prevailing were detected in the Mediterranean zone. 23 species mainly forest mezophils were found in the mountain-forest zone of the Crimea. The fauna of open mountain slopes is represented by 24 species of the family Coccinellidae. 14 species were detected in the yaila, Vibidia 12-guttata is the most typical one. Endemic species were not found in the Crimea.